Arthroscopic surgery of the knee. - Dandy, D J (1982)
In the first 1000 arthroscopic operations performed by one surgeon 136 patients had two or more procedures, making a total of 1168 during the 1000 operations. The indications for operation were internal mechanical derangements in 565 patients, anterior knee pain in 246, disorders of the synovium in 77, ligament injuries in 63, and degenerative joint disease in 49. Complications included fracture of instruments in the knee in five patients, haemarthrosis in 10, deep vein thrombosis in three, and synovial fistula in one. In no patient was the wound infected. A total of 26 different operations was performed.